The Vaccinia Virus A9L Gene Encodes a Membrane Protein Required for an Early Step in Virion Morphogenesis - Yeh, Wendy W. (American Society for Microbiology, 2000)
The A9L open reading frame of vaccinia virus was predicted to encode a membrane-associated protein. A transcriptional analysis of the A9L gene indicated that it was expressed at late times in vaccinia virus-infected cells. Late expression, as well as virion membrane association, was demonstrated by the construction and use of a recombinant vaccinia virus encoding an A9L protein with a C-terminal epitope tag. Immunoelectron microscopy revealed that the A9L protein was associated with both immature and mature virus particles and was oriented in the membrane with its C terminus exposed on the virion surface. To determine whether the A9L protein functions in viral assembly or infectivity, we made a conditional-lethal inducible recombinant vaccinia virus. In the absence of inducer, A9L expression and virus replication were undetectable. Under nonpermissive conditions, viral late protein synthesis occurred, but maturational proteolytic processing was inhibited, and there was an accumulation of membrane-coated electron-dense bodies, crescents, and immature virus particles, many of which appeared abnormal. We concluded that the product of the A9L gene is a viral membrane-associated protein and functions at an early stage in virion morphogenesis.